De la cultura de masas a la cultura mediática un análisis de los media desde la comunicación (2004)
This paper pretends to show the transition of the mass culture concept to the mediate culture concept. In that process playes a very important the mass media and the information and communication technology that moves the person of the communication, who is seen as an abstract and an amorphous person at the mass culture, to a person that produces sense from the consumption like a potential Emerec (émetteur-récepteur): sender-receiver. The development of this concepts will be done through the critical reconstruction of the history development of the analysis of the media and the information and communication technology. This writing is done from the Communication, thinking it as its fundamental epistemology competence.